Data mapping on ageing in low- and middle-income countries in Asia and the Pacific - TEERAWICHITCHAINAN, Bussarawan Puk (Institutional Knowledge at Singapore Management University, 2015)
Population ageing is an increasingly important demographic, social, and economic issue for researchers and policy makers throughout developing Asia prompting a need for data to monitor change and formulate evidence-based policies. There have been increasing endeavors in the Asia-Pacific region to collect information specifically related to older persons through representative surveys. These surveys are either broadly comprehensive or focus on particularly important domains, especially health. However, there is no systematic accounting of what the datasets address; to what extent different sources overlap or complement one another; how comparable they; and what data gaps remain. In addition, other data sources not specifically directed towards the older population can be useful in providing relevant information. Commissioned by HelpAge International with funding from UNFPA, this study documents the existence of data related to ageing issues as provided by surveys of older persons, censuses, and Demographic and Health Surveys (DHS) for 25 low- and middle-income AsiaPacific countries, namely Bangladesh, Bhutan, Cambodia, China, Cook Islands, DPR Korea, Fiji, India, Indonesia, Iran, Lao PDR, Malaysia, Maldives, Mongolia, Myanmar, Nepal, Pakistan, Palau, Philippines, Solomon Islands, Sri Lanka, Tonga, Thailand, Tuvalu, and Vietnam. The study was conducted by Bussarawan Teerawichitchainan of the School of Social Sciences, Singapore Management University; and John Knodel of the Population Studies Center, University of Michigan. Section 1 describes the objectives and scope of the report. A review of the demographic background in the 25 countries in section 2 reveals that surveys focusing on older persons tend to be carried out where population ageing is most advanced. This suggests that in countries where the share of the population in older ages is modest there is less interest with issues related to older persons. Yet countries with the lowest proportion of the population in older ages and most modest projected increases in this proportion nevertheless are projected to experience greater proportionate increases in the absolute number of older persons than those with more rapid population ageing. Burgeoning numbers of older persons will pose major challenges to the health, welfare and other support systems and thus deserve attention even if their share of the total population remains modest. In section 3 the authors systematically evaluate the content of data sources for the period from 2000-2014. Censuses were taken in all but Pakistan. DHS are available for 16 of the 25 countries. Both censuses and DHS provide information on the basic socio-demographic characteristics of older persons and of the households in which they live. Censuses also typically ask about disability status. Only 10 countries have comprehensive surveys of older people. Bangladesh, Cambodia, Indonesia, Maldives, Myanmar, the Philippines and Vietnam had one survey since 2000. India has had two, and China and Thailand have had multiple ageing surveys during this period. Some of the surveys are part of broader collaborations to build data infrastructure. The first, led by the World Health Organization, is the Study on global ageing and adult health (SAGE), involves longitudinal surveys focused on health. The second are broad aging surveys conducted in junction with the US-based Health and Retirement Study (HRS). Section 4 shows the key data gaps across the region and a need for more longitudinal data is noted. In the health domain, information on biomarkers, cognitive testing, and mortality are usually unavailable in current surveys. While the surveys attempt to capture economic activities of older people, the reasons for ceasing employment and retiring completely is not fully explored. Regarding income, often surveys capture this with just a few questions, though more detailed questions on revenues and expenditures would give a more accurate picture of income and consumption. The economic status of a household is a more appropriate indicator of material wellbeing than individual income. For family support, generally only limited information about monetary support received from family members, especially children, is asked and sometimes other types of support are probed as well. More rarely, the support and contributions that older people provide to their family and households are considered. Elder abuse is understudied and based on self-reports that may be influenced by a reluctance to report abuse by family members. Section 5 looks at data comparability and accessibility. Comparability is far easier when surveys are part of an international collaboration but is also feasible for those conducted independently. Some data sets are made publicly available. There is a trend to increase public access although historically this has not typically been the case. Section 6 describes good practices for data collection. 1) Promote contact from the beginning of the research process between those that conduct research on ageing and those that utilize the results. 2) Ensure that the design and implementation produces objective data and analysis. 3) Hold dissemination events. 4) Make data available to potential users. 5) Harmonize questionnaires to facilitate comparative analysis 6) Ensure data collection include modules to address specific issues of critical national interest. 7) Repeat ageing surveys periodically and adjust content to changing contexts. 8) Utilize relevant data available from surveys that do not focus on older persons. Section 7 concludes that surveys of older persons are useful for evidenced-based policy formulation even in countries where population ageing is modest and recommends the following:  The characteristics and situation of older persons should be routinely included as one topic in thematic reports that typically are issued following a census  Public use samples of census data should be made widely available to permit customized analyses of the older population.DHS should add a short module concerning the health of older persons  It is possible to expand existing longitudinal surveys not specifically designed to study ageing to cover issues pertaining to older persons  Funding agencies and donors should encourage careful documentation of ageing survey methodology (including sufficient information about sampling frame and procedure)  Gender analysis should incorporate issues specific to men as well as to women  International organizations and NGOs such as the UNFPA, World Bank, and HelpAge International can and should play a significant role in fostering communications among researchers in the Asia-Pacific region. Accompanying the main report are three Excel files providing data mapping details for three main categories of data sources:  Ageing surveys  National censuses  Demographic and Health Surveys